Do IgA nephropathy presentations display any seasonality? - Adrian Y. S. Lee; Ming-Wei Lin (Journal of Nephropathology, 2021)
IgA nephropathy (IgAN) is the most common glomerulonephritis and one of the most common causes of chronic kidney disease worldwide. Although IgAN has been classically linked with respiratory tract infections (RTIs), little studies have examined the epidemiology of this condition in terms of seasonal variations in presentations. We present the first study in one of Australia’s largest hospitals looking at the seasonality of this common condition. In summary, we surprisingly do not find any seasonal variations in the biopsy-proven presentation of this condition across 6 years of data.